THE INFLUENCE OF COMIC MEDIA BASED ON ADOBE PHOTOSHOP CS ON WRITING SKILLS AND LEARNING INTEREST OF CLASS IV SDN SIDOMULYO STUDENTS 05 - Fitriana Veni (Journal of Education Technology and Inovation, 2022)
This study aims to determine the effect of comic media based on Adobe Photoshop CS on writing skills and learning interest of fourth grade students of SDN Sidomulyo 05, Silo-Jember District.The phenomenon that exists in grade IV SDN Sidomulyo 05 is that there are several problems found in learning essay writing and a lack of interest in participating in learning activities. The problems encountered include: (a) there are still many students who have difficulty expressing their thoughts, feelings and ideas in writing in writing, (b) not being able to use solid sentences, (c) not being able to use correct spelling, (d) lack of interest in writing activities or tend to get bored easily because there are no more ideas that can be expressed in their writing, (e) students are not active in participating in essay writing activities and joke more with their friends. This study uses a causal quantitative research approach (cause and effect) in looking at the relationship of variables to the object under study, so that in this study there is an independent variable (X) namely comic media and two dependent variables, namely writing skills (Y1) and interest in learning (Y2). Techniques to determine a sample from a population that has certain characteristics to the desired quota. From this technique the researchers took a sample of class IV as many as 30 students. With the help of SPSS v.22 the results of the data obtained through the calculation of the SPSS test t-test, the t-count value of the conventional learning method has a value of -2.900 with a probability of 0.008 (sig). The mean difference in the conventional method is -2.30769 with a df of 25. Meanwhile, the t-count value in the comic media based on the Adobe Photoshop CS program is 6.325 with a probability of 0.001 (sig). The number of df is 25 with a mean difference of 4.61538. Meanwhile, from the results of the questionnaire data analysis of interest in learning obtained 0.535, this means that 53.5% of the data both have a positive effect. Based on the results of analysis and hypothesis testing, data obtained that Ho is rejected, which means that there is an effect of using adobe photoshop-based comic media on students' writing skills and interest in learning